2017
DOI: 10.1161/jaha.117.006224
|View full text |Cite|
|
Sign up to set email alerts
|

Plasma Nitrate and Incidence of Cardiovascular Disease and All‐Cause Mortality in the Community: The Framingham Offspring Study

Abstract: BackgroundNitrate is a dietary component as well as an endogenously formed metabolite and source of the signaling molecule nitric oxide. Harmful as well as beneficial effects of nitrate have been advocated. Data regarding the prognostic relevance of plasma nitrate are limited. The aim of this study was to evaluate the prospective association of plasma nitrate with cardiovascular disease (CVD) and all‐cause mortality.Methods and ResultsWe assayed plasma nitrate in 2855 Framingham Offspring Study participants (m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
22
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 66 publications
(196 reference statements)
5
22
1
1
Order By: Relevance
“…Our findings are very similar to a recently published Framingham Offspring Study that demonstrated association between elevated plasma levels of nitrate with total mortality and lack of association with incident cardiovascular disease . The study did not report the data on cardiovascular mortality and associations of NOx levels with mortality were not assessed in men or women separately …”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Our findings are very similar to a recently published Framingham Offspring Study that demonstrated association between elevated plasma levels of nitrate with total mortality and lack of association with incident cardiovascular disease . The study did not report the data on cardiovascular mortality and associations of NOx levels with mortality were not assessed in men or women separately …”
Section: Discussionsupporting
confidence: 89%
“…25 Our findings are very similar to a recently published Framingham Offspring Study that demonstrated association between elevated plasma levels of nitrate with total mortality and lack of association with incident cardiovascular disease. 26 The study did not report the data on cardiovascular mortality and associations of NOx levels with mortality were not assessed in men or women separately. 26 In general, serum levels of NOx are a steady-state sum of various dynamic processes including excretion of NOx from the body, oxidation of endogenous NO into NOx and dietary consumption of NOx.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For those with 4 or more cardiovascular risk factors, the plasma nitrate concentration was 35±4 μmol/L and plasma nitrite concentration was 171±29 nmol/L (both P <0.001). This higher plasma nitrate concentration with increasing numbers of cardiovascular risk factors appears to be similar to the findings by Maas et al . With increasing numbers of cardiovascular risk factors, plasma nitrite appears to be lower.…”
Section: Introductionsupporting
confidence: 90%
“…In this issue of JAHA , the examination by Maas et al of plasma nitrate and incidence of cardiovascular disease and all‐cause mortality from the Framingham Offspring Study is the largest data set using a robust measure of plasma nitrate performed to date, with a median follow‐up of 17.3 years …”
Section: Introductionmentioning
confidence: 99%